Sexual behavior and sexually transmitted diseases among the female partners of inmates - Debora Cristina Martins; Giovanna Brichi Pesce; Giordana Maronezzi da Silva; Carlos Alexandre Molena Fernandes (Universidade de São Paulo, 2018)
ABSTRACT Objective: to analyze the sexual behavior of the female partners of inmates and estimate the prevalence of sexually transmitted diseases. Method: cross-sectional, quantitative study involving 349 female partners of inmates. The Estudo de Comportamento Sexual [Sexual Behavior Study], an instrument validated in Brazil, was used to collect the data. The Statistical Package for the Social Sciences, version 20 was used in the statistical analysis. Results: 41.2% of the female partners of inmates reported a prior history of sexually transmitted disease. Association was found between having more than one partner in the last 12 months (<0.006), sexual violence (<0.001), having sex for money (<0.001), under the influence of alcohol (<0.001), and under the influence of drugs (<0.005). The variables associated with sexually transmitted infections in the logistic regression were: having more than one partner in the last 12 months, sexual violence, sex for money, and under the effect of alcohol or drugs. Conclusion: The number of partners, sexual violence, sex for money, and under the influence of alcohol or drugs are sexual risk behaviors that increase the prevalence of sexually transmitted infections among the female partners of inmates.